Sort by

- Relevance
- |Time

You have that: dv/dt =

**k***v^2 and you should already be able to tell that**k**is going to be a... that when v = 5 m/s, dv/dt = -1 m/s^2, so: -1 m/s^2 =**k***(5 m/s)^2**k**= -1/(25 m) The original differential equation is separable: v^(-2) dv...1 Answers · Science & Mathematics · 20/10/2009

... about the Arrhenius equation as the model, correct?

**k**= A0 * Exp( Ea / RT ) where**k**...) * (1/T) + ln A0 If we let y = ln**k**b = ln A0 m = Ea / R x = 1/T...1 Answers · Science & Mathematics · 05/10/2009

The period (T1) of a mass (m1) on a spring(

**k**) is: T1 = 2 pi sqrt (m1/**k**) Solve for...proportional to the square of the period (instead of plugging in**k**and canceling). Anyway, they give you the...1 Answers · Science & Mathematics · 26/02/2010

Use conservation of energy (

**K**+ U)1 = (**K**+ U)2 K1 = 0 and U1 = 0 (Set...1 Answers · Science & Mathematics · 05/03/2011

### phisics problem:a drop with primary radius r0 falls from height and gets moisture from air dm/dt=

**ks**?... know that the drop gains mass according to: dM/dt =

**k***S =**k***4*pi*r^2 Substitute the expression for the mass as a function...2 Answers · Science & Mathematics · 27/06/2006

1)

**k**= Force/ displcement = NEwton / m = kg m /(s^2 m) = kg /s^2 so dimensional formula [ M^1 T^-2] 2)**k**= Force/ Velocity ^n = kg m s^n __________ (s^2)(m^n) = kg m...2 Answers · Science & Mathematics · 11/01/2011

**K**.E = 1/2mv^2 wher, m is mass = 1 kg v is velocity = 6m/s**K**.E = 1/2(1)(6)^2**K**.E = 1/2(36)**K**.E = 18 joules1 Answers · Science & Mathematics · 22/10/2012

Given: f(E)=e^(-(E/(

**k**∗T))−(b/√E)) = {e^(-(E/(**k**∗T)))}{e^−(b/√E...)v(E) + u(E)v'(E) d{f(E)}/dE = {-(1/(**k**∗T)e^(-(E/(**k**∗T)))}{e^−(b/√E)} + {e^(-(E/(**k**...1 Answers · Science & Mathematics · 12/02/2013

"The Isotope potassium

**K**(atomic number = 40 mass number = 19)"... new element (Z=18) is argon. So**K**-40 has turned in Ar-40. We...2 Answers · Science & Mathematics · 18/12/2011

for spring restorative force F = -

**k**x m dv / dt = -**k**x dv = -**k**/m x dt dv = -**k**/m x {dx/v} v dv = -**k**/m dx...0 (spring retreats after reaching amplitude ------------------------- 0 = -**k**/m (a^2) + c1 >>> c1 put back (v^2) = -**k**/m (x^2) +**k**/m (a^2) v^2 =**k**...2 Answers · Science & Mathematics · 27/04/2007